Current assembly can mend ties between Umno and PAS - The Edge Financial, Daily (The Edge Financial Daily, 2016)
KUALA LUMPUR: Improving ties between Umno president Datuk Seri Najib Razak and PAS president Datuk Seri Abdul Hadi Awang will be seen as an inspiration to grassroots members to cooperate in the national interest and that of the ummah.